So...I previously found the series for $ f(t)= \begin{cases} 0&\text{if}\, -\pi\leq t\lt -\pi/2\\ \cos(t)&\text{if}\, -\pi/2\leq t\leq \pi/2\\ 0&\text{if}\, \pi/2\lt t\leq \pi\\ \end{cases} $

Where its period,$T$, is $2\pi$ and thus $w=2\pi/T=1$, and its series is:


I should be able to "easily" find the sum of the series of $\sum_{n=1}^∞\frac{(-1)^{n+1}}{4n^2-1}$ by using Parseval's identity exclusively

I know, by Parseval, and after some simplification, that $\sum_{n=2}^∞\frac{-2\cos(\frac{n\pi}{2})}{\pi(n^2-1)}\cos(nt)$=$\frac{\pi-2}{2\pi}$

But I am struggling at actually simplifying $\sum_{n=1}^∞\frac{(-1)^{n+1}}{4n^2-1}$ to the point that I am thinking that something here is wrong. So far, I have:


I am not sure if/how I should be evaluating $t$ in my original series, maybe that way I can make $-\cos(n\pi)=\cos(\frac{n\pi}{2})cos(nt)$ and afterwards somehow simplify the divisor?

Any suggestions/corrections are welcome

Edit 1:

By evaluating $t=\pi/2$ on the original series, I have:


Which is somewhat promising, though I haven't been able to far to make it similar to the desired series. I have tried messing with partial fractions and checking for patterns on how they evaluate for the first $n$'s, but no luck so far.

  • $\begingroup$ I think you should set $t = \frac{\pi}{2}$ and use double angle formulae to get $\cos(n \pi)$. $\endgroup$ – fGDu94 May 13 '19 at 10:39
  • $\begingroup$ Thanks! Indeed that gets it closer, though no luck so far, I added more info on the Edit. $\endgroup$ – Lightsong May 15 '19 at 8:44

You have shown that the series for $f(t)$ is $$ f(t)\sim \frac{1}{2}+\frac{1}{\pi}+\sum_{n=2}^{\infty}\frac{-2\cos\frac{n\pi}{2}}{\pi(n^2-1)}\cos(nt). $$ The terms of the sum are $0$ for $n=3,5,7,\cdots$. So, $f$ may be written as $$ f(t) \sim \frac{1}{2}+\frac{1}{\pi}+\sum_{k=1}^{\infty}\frac{-2\cos(k\pi)}{\pi(4k^2-1)}\cos(2kt) \\ \;\;\;\;\;\;= \frac{1}{2}+\frac{1}{\pi}-2\sum_{k=1}^{\infty}\frac{(-1)^{k+1}}{\pi(4k^2-1)}\cos(2kt) $$ The function $f$ is continuous and differentiable at $t=0$. So $f(0)$ is equal to the Fourier series. $f(0)=1$ gives $$ 1 = \frac{1}{2}+\frac{1}{\pi}-2\sum_{k=1}^{\infty}\frac{(-1)^{k+1}}{\pi(4k^2-1)} \\ \frac{\pi}{2}\left(\frac{1}{\pi}-\frac{1}{2}\right)=\sum_{k=1}^{\infty}\frac{(-1)^{k+1}}{4k^2-1} $$

| cite | improve this answer | |
  • $\begingroup$ Wow, thanks! That was quite tricky to get. Why did you square $\pi$ in the second step on the series denominator though? $\endgroup$ – Lightsong May 17 '19 at 8:49
  • $\begingroup$ @Lightsong : That looks like a mistake. Suddenly just replaced $\pi$ with $\pi^2$. So I just changed it. The tricky part was making sure to get the Fourier series right, which is what you already did. $\endgroup$ – COVID-20 May 17 '19 at 11:20

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.